2020
DOI: 10.1089/thy.2019.0490
|View full text |Cite
|
Sign up to set email alerts
|

A Thyroid Genetic Classifier Correctly Predicts Benign Nodules with Indeterminate Cytology: Two Independent, Multicenter, Prospective Validation Trials

Abstract: Background: Although most thyroid nodules with indeterminate cytology are benign, in most of the world, surgery remains as the most frequent diagnostic approach. We have previously reported a 10-gene thyroid genetic classifier, which accurately predicts benign thyroid nodules. The assay is a prototype diagnostic kit suitable for reference laboratory testing and could potentially avoid unnecessary diagnostic surgery in patients with indeterminate thyroid cytology. Methods: Classifier performance was tested in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…This type of testing takes a different approach from that of ThyroSeq v3 and Veracyte Afirma which require the original institution to submit the sample for molecular testing to centralized laboratories. Recent independent studies of international cohorts reported NPVs of 96% and 94%, which would be acceptable as "rule out" tests (36). However, additional independent studies for the 10gene panel (thyroid genetic classifier) with detailed performance characteristics and cost comparisons to the other molecular panels would be of interest.…”
Section: Molecular Testingmentioning
confidence: 99%
“…This type of testing takes a different approach from that of ThyroSeq v3 and Veracyte Afirma which require the original institution to submit the sample for molecular testing to centralized laboratories. Recent independent studies of international cohorts reported NPVs of 96% and 94%, which would be acceptable as "rule out" tests (36). However, additional independent studies for the 10gene panel (thyroid genetic classifier) with detailed performance characteristics and cost comparisons to the other molecular panels would be of interest.…”
Section: Molecular Testingmentioning
confidence: 99%
“…On average, 15%-25% of the nodules with indeterminate cytology that are operated on are malignant. About 60% of them are PTC, of which up to 10% require totalization (28)(29)(30). Between 10%-15% are FTC; information on indication to totalization is scarce in this setting (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…4,5,12,13 Some of these tests are now being used routinely in clinical practice, particularly in the United States, to rule out malignancy claiming false negative rates similar to that of benign cytology. [14][15][16][17][18] However, the predictive values of any diagnostic test are influenced by the pretest risk of malignancy. 19 Therefore, clinical, radiological and cytological information that precedes the molecular test needs to be considered for the indication and correct interpretation of the molecular test's results.…”
Section: Molecular Tests For the Evaluation Of Cytologically Indeterm...mentioning
confidence: 99%